2018
DOI: 10.4158/ep171955.cr
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Melas with Midd: An Uncommon Age of Presentation

Abstract: Objective: Maternally inherited diabetes and deafness (MIDD) is a rare form of diabetes caused by a mutation in mitochondrial DNA, usually a point mutation at position 3243 in the leucine tRNA gene. This same mutation can cause a rare but severe syndrome called mitochondrial encephalomyopathy with lactic acidosis and stroke-like episodes (MELAS).Methods: We describe a case of MIDD with acute mitochondrial decompensation that progressed to MELAS.Results: A 63-year-old male with MIDD and a history of hypoglycemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…There remains a question regarding the different consequences of MELAS and MIDD despite being associated with the same mutation. Previous case studies have shown that MIDD patients are likely to exhibit a low heteroplasmy of mutated DNA [120][121][122]; however, apart from this finding, no other direct evidence has been found to provide a clear explanation.…”
Section: Neurological Symptoms Cardiac Dysfunction Dyspraxiamentioning
confidence: 57%
“…There remains a question regarding the different consequences of MELAS and MIDD despite being associated with the same mutation. Previous case studies have shown that MIDD patients are likely to exhibit a low heteroplasmy of mutated DNA [120][121][122]; however, apart from this finding, no other direct evidence has been found to provide a clear explanation.…”
Section: Neurological Symptoms Cardiac Dysfunction Dyspraxiamentioning
confidence: 57%
“…To the best of our knowledge, hypotension attributed to a component of autonomic dysfunction in MELAS patients was first reported by Zelnik et al [15]. Subsequently, hypotension was occasionally reported, with these case studies providing more specific underlying causes for hypotension (for example, hypothyroidism [32] and sepsis [33]), and the blood pressure abnormalities or variations were not discussed in-depth. On the contrary, adult MELAS patients have been reported with elevated rates of hypertension [34].…”
Section: Discussionmentioning
confidence: 99%